Gypsies: pentecostalism and health. The Vie et Lumière Evangelical Church - Ramírez Hita, Susana (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Gypsies: pentecostalism and health.The Vie et Lumière Evangelical Church